(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article explores the importance of developing pre-service philology students’ corpus literacy skills through various methods. The authors discuss the benefits of incorporating corpus linguistics into the curriculum, such as improving students’ ability to analyze language patterns and trends. They also highlight different approaches to teaching corpus literacy, including hands-on activities and technology-based tools. Overall, this research emphasizes the value of equipping future philologists with the necessary skills to navigate and utilize corpora effectively in their academic and professional endeavors.